Decline of Interest Rates under Inflation Targeting and Previous Regimes: Evidence from Latin America and Developed Countries - Chión Chacón, Sergio Julio; Álvarez García, Kevin Antonio (Ekonomika, 2025)
This study empirically investigates the impact of Inflation Targeting (IT) on nominal interest rates over the past 40 years, focusing on 10 advanced and emerging economies. By using a Binary Regime Model embedded within a Backward-Looking Taylor, our findings confirm that IT adoption has significantly contributed to reducing interest rates, with the strongest effects observed in Latin American countries. To reinforce these results, we incorporate Smooth Transition Regression (STR) models, with and without instrumental variables, allowing for a more suitable representation of gradual policy transitions. The STR estimates consistently support our main findings, validating the robustness of the observed impacts. Furthermore, we show that, both before and after IT implementation, central banks display a stronger emphasis on responding to inflation than to the output gap, with this focus intensifying under IT regimes.